Transformasi budaya organisasi sebagai strategi adaptif lembaga keuangan syari’ah : studi literatur multidisiplin - Fadjar, Fahmi ilham (Maliki Interdisciplinary Journal, 2025)
Organizational culture is one of the key elements that influences the dynamics and performance of a company, one of which is Islamic financial institutions. Organizational culture is a collection of values that helps organizational members understand acceptable and unacceptable actions in the organization. .In simple terms, organizational culture can be defined as the values, norms, beliefs and practices that develop within an organization. Organizational culture transformation refers to deep changes in the values, norms, and practices that exist within an organization. In the context of sharia financial institutions, this transformation aims to align the institution’s operations with sharia principles and be responsive to customer needs. Transforming organizational culture is an urgent need for Islamic financial institutions in an increasingly dynamic era. Visionary leadership, a fair reward system, and effective communication will strengthen this transformation process. Although challenges such as resistance to change and consistency of implementation remain, if managed well, organizational culture transformation can improve the performance and competitiveness of Islamic financial institutions.